2009
DOI: 10.1200/jco.2009.22.8510
|View full text |Cite
|
Sign up to set email alerts
|

Placebo-Controlled, Double-Blind, Prospective, Randomized Study on the Effect of Octreotide LAR in the Control of Tumor Growth in Patients With Metastatic Neuroendocrine Midgut Tumors: A Report From the PROMID Study Group

Abstract: Octreotide LAR significantly lengthens time to tumor progression compared with placebo in patients with functionally active and inactive metastatic midgut NETs. Because of the low number of observed deaths, survival analysis was not confirmatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
1,639
5
69

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,194 publications
(1,751 citation statements)
references
References 38 publications
38
1,639
5
69
Order By: Relevance
“…In striking contrast to the compelling experimental evidence gathered in favor of a potential clinical and therapeutic benefit for SST in breast cancer, and despite the successful application of SST analogs to treat pituitary adenomas and neuroendocrine tumors (Rinke et al, 2009;Ben-Shlomo and Melmed 2010), the early, scarce clinical studies reporting treatment of breast cancer patients with SST analogs only demonstrated, at best, a limited success (Watt et al, 2008). Here, we provide evidence that a new factor in the SST/ssts system, sst5TMD4, is present in breast cancer, where it may counteract normal inhibitory function of SST/sst2 signaling.…”
Section: Introductionmentioning
confidence: 90%
“…In striking contrast to the compelling experimental evidence gathered in favor of a potential clinical and therapeutic benefit for SST in breast cancer, and despite the successful application of SST analogs to treat pituitary adenomas and neuroendocrine tumors (Rinke et al, 2009;Ben-Shlomo and Melmed 2010), the early, scarce clinical studies reporting treatment of breast cancer patients with SST analogs only demonstrated, at best, a limited success (Watt et al, 2008). Here, we provide evidence that a new factor in the SST/ssts system, sst5TMD4, is present in breast cancer, where it may counteract normal inhibitory function of SST/sst2 signaling.…”
Section: Introductionmentioning
confidence: 90%
“…SSAs have also been shown to exert a cytostatic effect, which can result in disease stabilization and the lengthening of the median time to tumor progression [92].…”
Section: Somatostatin Analogues and Peptide Receptor Radiotherapymentioning
confidence: 99%
“…Although shown to delay time to tumor progression, there is currently no evidence of improved survival in such patients. 21 Interferon a, like octreotide, has demonstrated antisecretory and antiproliferative effects on metastatic NETs. However, the data is insufficient to recommend its routine use in these patients.…”
Section: Metastatic Diseasementioning
confidence: 99%